Numbers and distribution of wintering waterfowl in Norway - NygÃ¥rd, Torgeir; Larsen, Bjorn Harald; Follestad, Arne; Strann, Karl-Birger (Wildfowl, 1988)
The Norwegian coast is important as a wintering area on the European scale for a number of waterfowl species, especially the marine diving ducks. The most important are the Common Eider, King Eider, Steller's Eider, Velvet Scoter, and the Red-breasted Merganser, all of these constituting more than 10% of the NW European stock. The Whooper Swan numbers are also quite high, due to its ability to use sheltered saltwater areas. The conditions in winter are unfavourable for most geese, which are found in very small numbers. Surface-feeders like the Mute Swan and the dabbling ducks prefer more sheltered, brackish or freshwater sites. Such areas are only found to a limited extent in the south-west, hence the number of these species groups are low on the European scale.